Pengaruh Profitabiltas, Likuiditas, Dan Solvabilitas Terhadap Financial Distress Pada Perusahaan Manufaktur - Novica, Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2021)
The purpose of this research is to obtain empirical evidence about the effects of profitability, liquidity, and solvability toward financial distress. This research is conducted by taking 78 manufacturing companies which listed on Indonesia Stock Exchange on 2017-2019. Sample was selected using purposive sampling method. Data processing techniques using multiple regression analysis that helped with E-Views 11.0 programs. The result showed profitability has a significant impact on financial distress while the other variable, liquidity and solvability showed insignificant impact on financial distress. The implication of this study is the need to increase the income and the sales and to decrease the liabilities that will decrease financial distress which will give a good signal for investors.